2011
DOI: 10.1071/en10056
|View full text |Cite
|
Sign up to set email alerts
|

Snow - a photobiochemical exchange platform for volatile and semi-volatile organic compounds with the atmosphere

Abstract: International audienceField and laboratory studies of organic compounds in snow (12 species; concentrations <= 17 μg L-1) were conducted and microorganisms in snow and aerosols at urban and Arctic sites were investigated (snow: total bacteria count <= 40000 colony forming units per millilitre (CFU mL(-1)), fungi <= 400 CFU mL(-1); air: bacteria <= 2.2 x 10(7) CFU m(-3), fungi <= 84 CFU m(-3)). Bio-organic material is transferred between snow and air and influence on snow-air exchange processes is demonstrated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 56 publications
0
41
0
Order By: Relevance
“…Recently, research pointed to ice nucleating activity of nanosized organic compounds, possibly peptides, as well as nanosized inorganic compounds such as metal oxides . In addition to the above categories of ice nuclei incorporated in the snow crystals, snowpack contains pollution particles Ariya et al 2011;Kos and Ariya 2010;Nemirovskaya and Kravchishina 2015;Radke et al 1980;Skeie et al 2011). These include aerosols from engine exhaust (Kuoppamäki et al 2014;Nazarenko et al 2015), power plants (Barrie 1980), mining activities (Williamson et al 2004), and other pollution sources.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research pointed to ice nucleating activity of nanosized organic compounds, possibly peptides, as well as nanosized inorganic compounds such as metal oxides . In addition to the above categories of ice nuclei incorporated in the snow crystals, snowpack contains pollution particles Ariya et al 2011;Kos and Ariya 2010;Nemirovskaya and Kravchishina 2015;Radke et al 1980;Skeie et al 2011). These include aerosols from engine exhaust (Kuoppamäki et al 2014;Nazarenko et al 2015), power plants (Barrie 1980), mining activities (Williamson et al 2004), and other pollution sources.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (e.g. Amato et al, 2007;Ariya et al, 2011) have reported various microbial groups and species living and actively functioning in snow. These microbes -algae, fungi and bacteria -may either produce or use VOCs, or affect the chemical reactions in which the VOCs participate.…”
Section: Sources and Sinks Of Snowpack Vocsmentioning
confidence: 99%
“…So far, only a few studies reporting measurements of snowpack gas concentrations have been published (e.g. Helmig et al, 2009a;Kos and Ariya, 2010;Ariya et al, 2011), and these studies have been focused mainly on VOCs other than terpenoids. Biogenic VOCs take part in air chemistry and are relevant also for climate change (Kulmala et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Snowpack VOC concentrations have been measured in a few studies (e.g. Kos and Ariya 2006, 2010, Ariya et al 2011, and most of these have been focused mainly on VOCs from anthropogenic sources. Karl et al (2009) even hypothesized that biogenic VOC emissions are close to zero and negligible during the snow cover period.…”
Section: Current Knowledge Of Forest Floor and Soil Voc Production Anmentioning
confidence: 99%